Enhancing the Glucose Flux of an Engineered EP-Bifido Pathway for High Poly(Hydroxybutyrate) Yield Production - Li, Ying; Sun, Zhijie; Xu, Ya; Luan, Yaqi; Xu, Jiasheng; Liang, Quanfeng; Qi, Qingsheng; Wang, Qian (Frontiers in Bioengineering and Biotechnology, 2020)
Background As the greenhouse effect becomes more serious and carbon dioxide emissions continue rise, the application prospects of carbon sequestration or carbon-saving pathways increase. Previously, we constructed an EP-bifido pathway in Escherichia coli by combining Embden-Meyerhof-Parnas Pathway, Pentose Phosphate Pathway and “bifid shunt” for high acetyl-CoA production. There is much room for improvement in the EP-bifido pathway, including in production of target compounds such as poly(hydroxybutyrate) (PHB). Result To optimize the EP-bifido pathway and obtain higher PHB yields, we knocked out the specific phosphoenolpyruvate phosphate transferase system (PTS) component ⅡCglc, encoded by ptsG. This severely inhibited the growth and sugar consumption of the bacterial cells. Subsequently, we used multiplex automated genome engineering (MAGE) to optimize the ribosome binding site (RBS) sequences of galP (galactose: H (+) symporter) and glk (glucokinase gene bank: NC_017262.1), encoding galactose permease and glucokinase, respectively. Growth and glucose uptake were partially restored in the bacteria. Finally, we introduced the glf (UDP-galactopyranose) from Zymomonas mobilis mutase sugar transport vector into the host strain genome. Conclusion After optimizing RBS of galP, the resulting strain L-6 obtained a PHB yield of 71.9% (mol/mol) and a 76 wt% PHB content using glucose as the carbon source. Then when glf was integrated into the genome strain L-6, the resulting strain M-6 reached a 5.81 g/L PHB titer and 85.1 wt% PHB content.